2014
DOI: 10.1016/j.lungcan.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of loss of quality-adjusted life expectancy (QALE) for patients with operable versus inoperable lung cancer: Adjusting quality-of-life and lead-time bias for utility of surgery

Abstract: a b s t r a c tObjectives: This study attempts to quantify the difference in loss of quality-adjusted life expectancy (QALE) for patients with operable and inoperable non-small-cell lung cancer (NSCLC). Patients and methods: A cohort consisting of 1652 pathologically verified NSCLC patients with performance status 0-1 was monitored for 7 years (2005)(2006)(2007)(2008)(2009)(2010)(2011) to obtain the survival function. This was further extrapolated to lifetime, based on the survival ratios between patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The current study measured the losses of QALE due to the combination of cognitive impairment and multimorbidity, and then discovered significantly additional burden from the interaction of cognitive impairment and multimorbidity at both individual and population levels. Unlike previous studies [26,43,44], our consequences were confirmed by losses of QALE based on the representative sample of a country rather than patient-based clinical studies.…”
Section: Discussionsupporting
confidence: 55%
“…The current study measured the losses of QALE due to the combination of cognitive impairment and multimorbidity, and then discovered significantly additional burden from the interaction of cognitive impairment and multimorbidity at both individual and population levels. Unlike previous studies [26,43,44], our consequences were confirmed by losses of QALE based on the representative sample of a country rather than patient-based clinical studies.…”
Section: Discussionsupporting
confidence: 55%
“…By using a semiparametric method explained in detail in our previous article [13], we extrapolated the survival to lifetime to estimate the life expectancy of patients receiving one of three first-line treatments. The extrapolation method has been shown to be effective via computer simulations [14], mathematical proof [15] and corroboration by examples of lung cancer cohorts [13,16,17]. The iSQoL statistical package (www.stat.sinica.…”
Section: Effectivenessmentioning
confidence: 92%
“…The curve of logit transformation of the relative survival between the index cohort and the reference population would follow an approximately straight line if the excess hazard of the patients remains constant over time (Fang, Chang, Hsu, et al, ). This method has been successfully validated with simulation data and has been used to analyze real data in several studies (e.g., Cucchetti, Trevisani, Bucci, et al, , Hung et al, , , H. Y. Lee et al, , Yang, Lee, Hsu, et al, ; Yang, Lai, Chang, et al, ). The assumption of an excess constant hazard, however, is usually untestable with a limited observed time period, because how closely the curve of logit‐transformed relative survival approaches a straight line is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been successfully validated with simulation data and has been used to analyze real data in several studies (e.g., Cucchetti, Trevisani, Bucci, et al, 2016, Hung et al, 2011, H. Y. , Yang, Lee, Hsu, et al, 2012Yang, Lai, Chang, et al, 2014). The assumption of an excess constant hazard, however, is usually untestable with a limited observed time period, because how closely the curve of logit-transformed relative survival approaches a straight line is uncertain.…”
mentioning
confidence: 99%